(3GdJgPjHs - (3GdMSjf Hf eSYhO Hf eMeO, GdaqQGA, Ch GHf GdnanqQGA, CHh eMeO, hjdbH HeMjj GdSqfI, GdHZhj,J (B510 (3g` s
(3ChdgG (B:s
(3cJGH GdbUGU s
(3ef GdfSNI faSgGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B259 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B61s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B11 - (3U (B296 s
(3eUOQ GbJfGA GdCUd (B:s
(3CMeO GdKGdK (B(870) s
Keywords: (3Gdabg GdTGaYjs